Velocity Dispersion, Size, Sérsic Index, and D n 4000: The Scaling of Stellar Mass with Dynamical Mass for Quiescent Galaxies - Zahid, H. Jabran; al., et (2017)
We examine the relation between stellar mass, velocity dispersion, size, Sérsic index, and [D]n4000 for a volume-limited sample of ∼40,000 quiescent galaxies in the SDSS. At a fixed stellar mass, galaxies with higher [D]n4000 have larger velocity dispersions and smaller sizes. [D]n4000 is a proxy for stellar population age, thus these trends suggest that older galaxies typically have larger velocity dispersions and smaller sizes. We combine velocity dispersion and size into a dynamical mass estimator, [σ ]2R. At a fixed stellar mass, [σ ]2R depends on [D]n4000. The Sérsic index is also correlated with [D]n4000. The dependence of [σ ]2R and Sérsic index on [D]n4000 suggests that quiescent galaxies are not structurally homologous systems. We derive an empirical correction for non-homology which is consistent with the analytical correction derived from the virial theorem. After accounting for non-homologous galactic structure, we measure [M]* [M]d0.998+/- 0.004, where M * is the stellar mass and M d is the dynamical mass derived from the velocity dispersion and size; stellar mass is directly proportional to dynamical mass. Quiescent galaxies appear to be in approximate virial equilibrium, and deviations of the fundamental plane parameters from the expected virial relation may result from mass-to-light ratio variations, selection effects, and the non-homology of quiescent galaxies. We infer the redshift evolution of velocity dispersion and size for galaxies in our sample assuming purely passive evolution. The inferred evolution is inconsistent with direct measurements at higher redshifts. Thus quiescent galaxies do not passively evolve. Quiescent galaxies have properties that are consistent with standard galaxy formation in ΛCDM. They form at different epochs and evolve modestly, increasing their size, velocity dispersion, and Sérsic index after they cease star formation.